(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2026)
This study aimed to determine the role of marketing innovation in its dimensions (product innovation, price innovation, promotion innovation, and distribution innovation) in improving the brand image in its dimensions dimensions (affective dimension, cognitive dimension, and behavioral dimension) in food industry companies in Al Hudaydah Governorate. The descriptive analytical method was used as the study method. The study population was the administrators working in the food industry companies (the subject of the study), numbering (403), and the number of respondents was (370). A questionnaire was developed to collect the data, and the data were analyzed and the hypotheses tested using the statistical analysis program (SPSS) as well as the program (AMOS24). The study concluded that there is a positive role for marketing innovation in improving the mental image in the food industry companies (the subject of the study), there is a positive role for price innovation and distribution innovation in improving the mental image in the food industry companies, and there is no positive role for product innovation and promotion innovation in improving the mental image in these companies. The study recommended that industrial companies continue to support and promote marketing innovation in industrial companies by developing new products, improving promotion strategies, and using modern technology in marketing to ensure an improved public image for the companies under study.